Per Fulvio Papi (Materiali di Estetica. Terza serie, 2024)
This article commemorates Fulvio Papi, highlighting his dual role as a philosopher and public intellectual. It elaborates on Papi's consistent integration of theoretical research with his public responsibilities, reflecting on his discreet yet firm personal style and his lifelong socialist ideals. Capelli appreciates Papi's avoidance of overt political engagements, focusing instead on a thoughtful cultural direction that influenced his academic and public roles. The tribute explores Papi's philosophical contributions and his enduring impact on cultural discussions, particularly through his roles at the Casa della Cultura and his influential writings.
Keywords: philosophy; Casa della Cultura; Fulvio Papi